Damascus - Burns, Ross, author.
1 online resource.
Keywords: Damascus, first published in 2005, was the first book in English to relate the history of the city, bringing out the crucial role it has played at many points in the region's past. It traced the history of this colourful, significant and complex city through its physical development, from the city's emergence in around 7000 BC through the changing cavalcade of Aramaean, Persian, Greek, Roman, Byzantine, Arab, Mongol and French rulers right up to the end of Turkish control in 1918. Now updated to place the city in the context of the events of the Syrian conflict post-2011, and to include the most recent scholarship on the long history of the city, this volume is a must-read for anyone interested in Syrian history and archaeology, and an ideal partner to Burns' Aleppo (Routledge, 2016). Lavishly illustrated, Damascus: A History remains a compelling and unique exploration of this fascinating city.